A correction to 'efficient and secure comparison for on-line auctions'. (1st September 2009) - Damgard, Ivan; Geisler, Martin; Kroigard, Mikkel
In this paper, we describe a correction to the cryptosystem proposed in Damgard et al. from Int. J. Applied Cryptography, Vol. 1, No. 1. Although, the correction is small and does not affect the performance of the protocols from Damgard et al., it is necessary, as the cryptosystem is not secure without it.